Primary care clinicians' perceptions of antibiotic resistance: a multi-country qualitative interview study. - Wood, F; Phillips, C; Brookes-Howell, L; Hood, K; Verheij, T; Coenen, S; Little, P; Melbye, H; Godycki-Cwirko, M; Jakobsen, K; Worby, P; Goossens, H; et al. (2013)
OBJECTIVES: To explore and compare primary care clinicians' perceptions of antibiotic resistance in relation to the management of community-acquired lower respiratory tract infection (LRTI) in contrasting European settings. METHODS: Qualitative interview study with 80 primary care clinicians in nine European countries. Data were subjected to a five-stage analytical framework approach (familiarization; developing a thematic framework from the interview questions and the themes emerging from the data; indexing; charting; and mapping to search for interpretations in the data). Preliminary analysis reports were sent to all network facilitators for validation. RESULTS: Most clinicians stated that antibiotic resistance was not a problem in their practice. Some recommended enhanced feedback about local resistance rates. Northern European respondents generally favoured using the narrowest-spectrum agent, motivated by containing resistance, whereas southern/eastern European respondents were more motivated by maximizing the potential of a rapid treatment effect and so justified empirical use of broad-spectrum antibiotics. Antibiotic treatment failure was ascribed largely to viral aetiology rather than resistant bacteria. Clinicians generally agreed that resistance will become more serious without enhanced antibiotic stewardship or new drug discovery. CONCLUSIONS: If current rates of antibiotic resistance are likely to result in important treatment failures, then provision of local resistance data is likely to enhance clinicians' sense of importance of the issue. Interventions to enhance the quality of antibiotic prescribing in primary care should address perceptions, particularly in the south and east of Europe, that possible advantages to patients from antibiotic treatment in general, and from newer broad-spectrum compared with narrow-spectrum agents, outweigh disadvantages to patients and society from associated effects on antibiotic resistance.